Catalytic dehydrogenation cracking of crude oil to light olefins by structure and basicity/acidity adjustment of bifunctional metal/acid catalysts. (15th February 2023) - Zhang, Di; Zong, Peijie; Wang, Jiaoyang; Gao, Hongwei; Guo, Jinzhuang; Wang, Jingxian; Wang, Yuxin; Tian, Yuanyu; Qiao, Yingyun
Highlights: Metal/acid catalysts with different structure and basicity/acidity were prepared. Catalytic cracking conversion of crude oil to light olefins was conducted by Py-GC/MS and a fluidized bed reactor. The coupling mechanism between metals and acid catalysts to form bifunctional catalysts was investigated. Cracking characteristics, apparent kinetics, and product adjustment mechanism of crude oil were analyzed by TG-FTIR. Abstract: Catalytic dehydrogenation cracking of crude oil to light olefins (CTO) was carried out by pyrolysis gas chromatography-mass spectrometry (Py-GC/MS) and a fluidized bed reactor. Cracking characteristics, apparent kinetics, and product release rules of CTO were analyzed by the thermogravimetric analyzer coupled with Fourier transform infrared spectroscopy (TG-FTIR). Results showed that dehydrogenation-cracking bifunctional catalysts could be obtained only when the properties of metals matched with acid catalysts. The bifunctional 1%Ca/ZSM-5 (1Ca/ZSM-5) catalysts can increase dehydrogenation, attenuate hydrogen transfer, and inhibit coking. Consequently, light ( C 2 -C4 ) olefins produced from 1Ca/ZSM-5 catalyst were enhanced significantly. There were mainly-two stages of pyrolysis and catalytic dehydrogenation cracking in the catalytic conversion of crude oil. The activation energy of bifunctional 1Ca/ZSM-5 catalyst decreased in the pyrolysis stage. The product adjustment mechanism by bifunctional catalysts was proposed from the perspective of structure and basicity/acidity, which would guide the maximization production of light olefins.